PEMANFAATAN PEMASARAN DIGITAL PADA HOME INDUSTRY KOPI SEPAKUNG - Shofif Sobaruddin A; Hawik Ervina; Sutrisno Sutrisno (Bajang Institute, 2022)
The covid pandemic that has hit the world for more than two years, continues to provide opportunities for home industry players, especially the coffee industry, to continue to develop their business online/digitally. The Sepakung Coffee Industry is a home industry located in Sepakung Village, Banyubiru District, Semarang Regency which carries regional superior products. This partnership community service activity takes an educational approach and digital marketing assistance as a marketing strategy breakthrough to sell Sepakung coffee products by utilizing the use of technology. This is because traditional marketing is no longer fully effective for markets where most people have switched to using communication technology. The digital-based marketing model is expected to be adopted by home industry players in marketing their products so that it can have an impact on increasing the income of micro businesses so that the MSME sector can further develop. the resulting product.